Representasi Keluarga di Bulan Ramadan dalam Iklan Gojek Indonesia - Muhammad Rafi Kalauw; Raditya Pratama Putra (UNISBA Press, 2023)
Abstract. Gojek makes the imaginative advertisements that they produce in the media easily accepted by the public and have added value in the form of humor, including trending on the internet. In this study, researchers conducted an analysis of how families are represented in the month of Ramadan in Gojek Indonesia's advertisement entitled Live Ramadan Gojek is ready to help on Gojek Indonesia's YouTube account. John Fiske's semiotic analysis technique is used in this research. In John Fiske's semiotics there are levels of reality, representation, and ideology. This research was conducted to determine the level of reality, representation, ideology, and find out the application of digital advertising in persuading audiences. Qualitative research methods are used in research so that they are concerned with aspects of understanding in depth of a problem. The approach in this research is John Fiske's semiotics. Semiotics is the study of signs in human life. The reality levels include Appearance, Costume and Make-up, Environment, Behavior, Dialogue and Movement represents Indonesian families in the month of Ramadan, the level of representation includes cameras and Voices Voice over and Backsound, in terms of cameras and sound represents the family situation during the month of Ramadan so that it has continuity in terms of audio-visual, the ideological level represents Islamic ideology, and the application of advertisements in persuading audiences There are two elements, namely elements of persuasive language and elements of humor. based on the results of this study it was found that in Jalananin Ramadan advertisements Gojek Ready to Help You already represents families in the month of Ramadan. Abstrak. Gojek membuat iklan imajinatif iklan yang mereka hasilkan di media mudah diterima oleh masyarakat dan memiliki nilai tambah berupa humor, diantaranya menjadi trending di internet. Dalam penelitian ini peneliti melakukan analisis bagaimana representasi keluarga di bulan Ramadan dalam iklan Gojek Indonesia berjudul jalanin Ramadan Gojek siap bantu di akun YouTube milik Gojek Indonesia. Teknik analisis semiotika John Fiske digunakan dalam penelitian. Dalam semiotika John Fiske terdapat level realitas, representasi, dan ideologi. Penelitian ini dilakukan untuk mengetahui level realitas, representasi, ideologi, dan mengetahui penerapan iklan digital dalam mempersuasi khalayak. Metode penelitian kualitatif digunakan pada penelitian sehingga mementingkan pada aspek pemahaman secara mendalam dari suatu problematika. Pendekatan dalam penelitian ini semiotika John Fiske. Semiotika ilmu mempelajari tanda dalam kehidupan manusia. Level realitas meliputi Penampilan, Kostum, dan Riasan, Lingkungan, Kelakuan, Dialog, dan Gerakan merepresentasikan keluarga Indonesia di bulan Ramadan, level representasi meliputi kamera dan Suara Voice over dan Backsound, dalam hal kamera dan suara merepresentasikan keadaan keluarga di saat bulan Ramadan sehingga memiliki ketersinambungan dalam hal audio visual, level ideologi merepresentasikan ideologi Islam, dan penerapan iklan dalam mempersuasi khalayak terdapat dua unsur yaitu unsur bahasa persuasif dan unsur humor. berdasarkan hasil dari penelitian ini ditemukan bahwa dalam iklan Jalananin Ramadan Gojek Siap Bantu Kamu sudah merepresentasikan keluarga di bulan Ramadan.